2015
DOI: 10.1563/aaid-joi-d-13-00036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poly-L-Lysine coating on titanium osseointegration: from characterization to in vivo studies

Abstract: Dental implant prostheses cannot preclude a correct and stable implant osseointegration, which is still a challenge and greatly depends on biomaterial-cell interface. Titanium (Ti) coating using polyelectrolyte poly-L-lysine (PLL) may represent an interesting and simple approach, to provide a charged surface net able to improve cell adherence. However, in vitro and in vivo effects of Ti coated with PLL have been poorly investigated. The aims of the present study are (1) to obtain and characterize, chemically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 27 publications
4
31
0
Order By: Relevance
“…The percentage ratio between the linear contact of the newly formed tissue including lamellar bone, woven bone and osteoid within the implants and the total perimeter of the implants was calculated on the same slides used for the stereological analysis in order to quantify the amount of osseointegration using a dedicated navigation software (Image J, NIH; Varoni et al, 2015). A mean value over the 10 photos was then computed and an average tissue to implant contact (TIC) was obtained for each section (Fabbro et al, 2017;Ragone et al, 2020).…”
Section: Histomorphometric Analysismentioning
confidence: 99%
“…The percentage ratio between the linear contact of the newly formed tissue including lamellar bone, woven bone and osteoid within the implants and the total perimeter of the implants was calculated on the same slides used for the stereological analysis in order to quantify the amount of osseointegration using a dedicated navigation software (Image J, NIH; Varoni et al, 2015). A mean value over the 10 photos was then computed and an average tissue to implant contact (TIC) was obtained for each section (Fabbro et al, 2017;Ragone et al, 2020).…”
Section: Histomorphometric Analysismentioning
confidence: 99%
“…Among the different variables, surface features are one of the most important factors, including physicochemical and topographical properties. Previous studies have shown that the modulation of the surface properties has enhanced the osseointegration of dental implants in the short and long term (4-7). In this sense, many studies suggest that microstructured and nanostructured topographies may better guide cell behavior compared with surface chemistry (8).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Varoni et al studied in vitro and in vivo effects of poly-L-lysine coating on titanium osseointegration. Such coating safely enhanced calcium deposition and implant early osseointegration in animals, suggesting promising evidence to optimize the surface properties of these dental implants [356]. Walters et al investigated the antimicrobial properties of poly(L-lysine) in mono/tricalcium phosphates-HA composites.…”
Section: Proteins and Poly(amino Acids)mentioning
confidence: 99%